Prohibition of Interfaith Marriage: An Analysis of Judicial Guidelines for Adjudicating Marriage Registration Applications Among Different Religions and Belief - Raja Asauqi Muhammad Yusuf; Fauziah lubis (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
Marriage in Indonesia aims to form a happy and lasting family, with its validity based on religious laws as per Article 2 Paragraph (1) of the Marriage Law. Despite this, interfaith marriages present legal ambiguities as some religions do not prohibit such unions, leading to varied judicial decisions and interpretations. The legal gaps in Indonesia's 1974 Marriage Law concerning interfaith marriages necessitate standardization in judicial practice. Supreme Court Circular Letter (SEMA) No. 2 of 2023 was issued to address these inconsistencies and provide clear guidelines for judges. This study utilizes qualitative descriptive analysis, combining literature reviews and interviews with judges at the Lubuk Pakam Religious Court, to assess the impact of SEMA No. 2 of 2023 on interfaith marriage registration cases. Judges possess ex officio rights to make decisions based on legal and logical considerations, ensuring justice and utility. The study found that religious institutions primarily handle marriage registration, with the Civil Registry Office recording only same-faith marriages and District Courts occasionally handling interfaith unions. The multi-interpretative nature of the Marriage Law leads to complex judicial and social implications in religiously diverse regions like Lubuk Pakam. SEMA No. 2 of 2023 aims to standardize judicial practices and provide legal certainty regarding interfaith marriages. Although it is primarily an internal directive, its influence extends to public awareness and judicial consistency. The study highlights the necessity for thorough understanding and dissemination of SEMA among judges to ensure lawful and uniform application.